Surviving the shift: a practical handbook for night shift healthcare workers - Clothier, Claire, author (Colorado State University. Libraries, 2024)
"Surviving the Shift: A Practical Handbook for Night Shift Healthcare Workers" is a comprehensive guidebook that provides information and guidance to those struggling with the lifestyle of night shift. It serves to highlight the adversity that healthcare workers face while working night shift. While examining extensive, peer-reviewed research, I focused on eight problematic topics associated with working night shift including sleep disruptions, diet and nutrition, exercise, gastrointestinal problems, cardiovascular disease, type 2 diabetes, hormonal imbalances, and social isolation. To select these topics, I familiarized myself with general research on night shift and compiled a list of the recurring issues workers face. In my digital guidebook, I introduced each topic, included scientific research, and defined important terms and concepts. Additionally, I critically analyzed the role of night shift in amplifying these common problems. By interpreting this scientific information as it related directly to night shift workers, I formulated a list with several tips to combat the negative impacts. At the close of my guidebook, I provided benefits of night shift, a sample 24-hour routine, as well as an interview with a registered nurse. Through all of this research and construction of my Honors Thesis, I determined that the underlying culprit for most of the physical and mental issues linked to night shift is the disruption to the body's circadian rhythm.
Colorado State University Honors Program. College of Health and Human Sciences: Health and Exercise Science, Sports Medicine Concentration, Adviser: Pamela Vaughan Knaus, Committee Member: Rick Perry.
Keywords: night shift; healthcare; shift work